Disseminated intravascular coagulation: A review of the topic - Hernández-Martínez, Alejandro; Martínez-Sanchez, Lina Maria (Universidad y Salud, 2018)
Introduction: Disseminated intravascular coagulation is a secondary syndrome to underlying pathologies, where localized coagulation activation and generalized inflammatory response can lead to tissue and microvascular damage. A prevalence of 10.8% has been reported in several intensive care units in Colombia. Its presentation in the context of sepsis is different depending on the type of infection. Objective: To conduct a review of literature of the most outstanding concepts of disseminated intravascular coagulation. Materials and methods: A review was made by means of the search of original articles, systematic and narrative reviews, in the PubMed and ScienceDirect databases and in the Google Scholar search engine; 80 articles were selected, of which 51 were included. Publications were taken into account in Spanish, English and French, with a publication date of less than or equal to 5 years. Results: The description of treatment, etiology, clinical presentation and diagnosis of Disseminated Intravascular Coagulation was made, with special emphasis on the studies on molecular markers and new therapeutic alternatives. Conclusion: Disseminated intravascular coagulation is a complication which contributes to increase morbidity and mortality, whose early diagnosis and treatment contribute significantly to better clinical evolution.